Kebijakan moneter: Teori dan bukti empiris - Iswardono Sardjonopermono (Economic Journal of Emerging Markets, 1998)
Monetary crisis accured in Indonesia has showed a serious weakness of monetary policy by Sentral Bank. As written in this paper, there are many weakness and mistakes of Sentral Bank as monetary policy maker in Indonesia.